The Relationship Among Pressure Ulcers, Oxygenation, and Perfusion in Mechanically Ventilated Patients in an Intensive Care Unit - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
PURPOSE: We examined the relationships among oxygenation, tissue perfusion, and other comorbid conditions not incorporated into the Norton Scale, and pressure ulcer (PU) development in subjects receiving mechanical ventilation. DESIGN: Descriptive, observational study. SETTING AND SUBJECTS: The setting was our university hospital's surgical/emergency intensive care unit in Istanbul province, Turkey. The sample comprised 30 patients who were older than 18 years, did not have a PU on admission, and had been mechanically ventilated for more than 24 hours when data collection began. METHODS: Skin integrity and a PU risk, using the Norton Scale, were administered twice daily. In addition, serum blood testing, vital signs, and data regarding ventilation and oxygenation status were obtained from the patient's electronic medical records. RESULTS: Slightly less than half of subjects were women (n = 14, 46.7%). Their mean age was 54.36 years (SD = 20.68). Pressure ulcers developed in 5 patients (16.7%); all PUs were located on the heel. All ulcers were initially observed as stage I lesions; 1 progressed to a stage II ulcer and 1 progressed to a stage III ulcer. Patients who developed pressure ulcers have higher serum glucose levels (z = -2.198; P = .028), higher serum pH levels (z = -2.031; P = .028), and lower diastolic blood pressures (z = 0.055; P = .057) than those who remained ulcer free. CONCLUSION: Our results demonstrate that mechanically ventilated patients who develop PUs were more likely to have significantly higher blood glucose levels, significantly lower diastolic blood pressure values, and significantly higher serum pH values than were patients who remained free of PUs. Nurses who care for mechanically ventilated patients should recognize these factors and initiate preventive interventions as indicated.
Keywords: PREVENTION